(untitled) (Medico Legal Update, 2019)
Background/Objectives: To form habits through the dental health education for assisting with mid to long-term oral health maintenance of elementary school students, surveys were conducted from March to December of 2018. Method/Statistical Analysis: The data was encoded then statistically analyzed using SPSS ver. 23.0, and the level of significance was set as 0.05. Cross-tabulation was conducted for the grade distribution depending on the gender, and the frequency analysis was conducted for the existence of oral health recognition, school’s oral health education behaviors and changes in toothbrushingbehaviors after the oral health education. Findings: As for dental health education, 74.8% students responded that it is ‘helpful’ for dental health care, and 71.7% students responded that it is ‘helpful’ for dental health education usage and method. As for dental health recognition, ‘healthy’ was the most frequent response, and 49.2% students responded they have experienced ‘bleeding from the gum’ when toothbrushing. As for the toothbrushing related questions, 35.5% respondents were using rotational method, and 54.1% responded that they brush after lunch. “between 2 to 3 minutes” was the most popular with 33.1%. As for the distribution of correct answers for dental health knowledge before and after education, the correct answers which asked ‘if the cause of gum disease is dental plaque’ increased after education(89.9%) compared to before (76.1%). The question which asked ‘if one should brush teeth before going to sleep’, the correct answer was higher after education(98.4%) compared to before (89.6%). The question which asked ‘if fruits, milk and vegetables assist with tooth cleanliness’, the correct answer was higher after education(88.2%) compared to before(79.4%). Improvements/Applications: Consequentially, forming proper habits through repeated education and